Analysis of Small Group and Individual Teaching Skills Students of Microteaching Learning - Saidah, Ika Nurul Afifatus; Ngazizah, Nur (Islamic Journal of Integrated Science Education (IJISE), 2022)
Small group and individual teaching is a form of learning that allows teachers to pay attention to each student, and establish a closer relationship between teachers and students as well as between students and students. This study aims to determine the ability of small group and individual teaching skills possessed by semester VI students of Primary School Teacher Education Study Program for the 2021/2022 academic year in the microteaching course. The basic teaching skills that must exist in a teacher or educator can be divided into eight types of skills. These skills play a very important role and determine the quality of learning, namely: explaining skills, opening and closing skills, questioning skills, skills to provide reinforcement, skills to carry out variations, skills to guide discussions and teach small groups and individuals, and skills to manage classes. To achieve the research objectives, the researcher used the type of research used was descriptive qualitative research to describe descriptively the basic teaching skills of prospective elementary school teacher students in microteaching courses involving 10 students. Data collection was done by direct observation in the form of a questionnaire given to students. Data were analyzed quantitatively and presented in tables.